(untitled) (Fiep Bulletin - online, 2014)
The lack of physical activity loses the human organism balance developing Hypocinesia syndrome which brings consequences such as appearance of several illness denominated illness of civilization, and among them the hypertension, illness that can take the people to death. The purpose of this research was to provoke if there is a difference in the development of aerobic capacity (VO max) of hypertensions and normal tensions women in Concórdia city. The sample of the research was compounded of 23 healthy 2 volunteer women from 45 to 65 age group (14 from 46 to 55 age group, and 9 from 56 to 65 age group) and 21 women with moderated hypertension in treatment (12 from 46 to 55 age group and 9 from 56 to 65 age group) from Concórdia city - SC. To determination of aerobic capacity (VO max) from individuals of the sample were used the Walking Test of 400m from Kalinina. To statistic treatment 2 were used the methods of statistical parametrical (average, pattern detour, Test “t” to independents samples). The level of reliable adopted is = 0,05. The results of the research showed that aerobic capacity (VO max) from hypertensions women of researched 2 sample, on average, is significant minor than normal tensions women. The difference reaches 27,1% (p < 0,01) from 45 to 55 age group and 29,9% (p < 0,01) from 56 to 65 age group, and the level of development of aerobic capacities of hypertensions women of the reached sample is very low. Conclusion: maybe the level very low of the development of aerobic capacities from women from 46 to 65 age group can provoke hypertension.